Analisis Kesulitan Berbicara Bahasa Arab Mahasiswa Tingkat Akhir Prodi Pendidikan Bahasa Arab Universitas Nurul Jadid Probolinggo - Yayah Robiatul Adawiyah; Rahmawati Rahmawati; Sri Wulandari; Inni Muthmainnah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Final year PBA students who have difficulty speaking Arabic have obstacles that show symptoms that can be observed by teachers/lecturers. Some symptoms that are signs of difficulty in Arabic include: students showing low performance whose position is below the average achieved by their group, students having difficulty speaking Arabic during presentations and thesis exams. The results achieved are not commensurate with the efforts made, are slow in carrying out coursework, show inappropriate attitudes such as: difficulty in communicating Arabic during presentations, skipping class one day and coming late to class. This research aims to obtain clarity regarding: 1. Factors that cause students to have difficulty speaking Arabic; 2. Appropriate alternative assistance efforts to overcome the Arabic language difficulties of final semester PBA students at Nurul Jadid University. This research is qualitative research with a case study approach. The data collection techniques used in this research are in-depth interviews, observations, and documentation studies with the main data source, namely final semester PBA students. The data obtained was then analyzed based on Milles and Hubermen's analysis flow, namely data reduction, data presentation, and conclusions or data verification. The results of the analysis of students' difficulty speaking Arabic were 60% due to internal factors, namely originating from within the human being, such as psychological factors, and 40% due to external factors in the form of social and non-social factors.